2008
DOI: 10.1080/09603100701537714
|View full text |Cite
|
Sign up to set email alerts
|

The impact of listing stock options on the underlying securities: the case of Taiwan

Abstract: Based on the asymmetric information and complete market hypotheses, this article attempts to explain the impact of listing stock options on the abnormal return, volatility, trading volume and market depth of the underlying securities in Taiwan. The empirical results find that positive abnormal returns exist, the degree of volatility decreases, trading volume increases and market depth also increases following the introduction of the stock options. The empirical results for the sub-sample are found to be consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Hayes and Tennenbaum (1979), Whiteside, Duke, and Dunne (1983), Ma and Rao (1988), Bansal, Pruit and Wei (1989), Conrad (1989), Skinner (1989), DeTemple and Jorion (1990), Damodaran and Lim (1991), Rao, Tripathy, and Dukes (1991), and Schultz and Zaman (1991) find that stock return volatility in U.S. markets is lower after option introduction. Similar results are found by Watt, Yadav, and Draper (1992) studying the UK market, Chaudhury and Elfakhani (1995) investigating the Canadian market, Stucki and Wasserfallen (1994) the Swiss markets, Sahlström (2001) studying Finnish stocks, and Chen and Chang (2008) Taiwan. Damodaran and Lim's (1991: 647) findings are representative of these results, reporting that "the listing of options leads to significantly lower (emphasis in the original) variance in the daily returns of the underlying stocks" Conversely, Kabir (1997) studying the Dutch market, Calado, Garcia and Pereira (2005) studying Portuguese markets and Mazouz and Bowe (2009) studying NYSE stocks listed on the CBOE find no significant change in risk following option listing.…”
Section: Hypothesis 2: Impact Of Options Listing On the Volatility Ofsupporting
confidence: 74%
See 1 more Smart Citation
“…Hayes and Tennenbaum (1979), Whiteside, Duke, and Dunne (1983), Ma and Rao (1988), Bansal, Pruit and Wei (1989), Conrad (1989), Skinner (1989), DeTemple and Jorion (1990), Damodaran and Lim (1991), Rao, Tripathy, and Dukes (1991), and Schultz and Zaman (1991) find that stock return volatility in U.S. markets is lower after option introduction. Similar results are found by Watt, Yadav, and Draper (1992) studying the UK market, Chaudhury and Elfakhani (1995) investigating the Canadian market, Stucki and Wasserfallen (1994) the Swiss markets, Sahlström (2001) studying Finnish stocks, and Chen and Chang (2008) Taiwan. Damodaran and Lim's (1991: 647) findings are representative of these results, reporting that "the listing of options leads to significantly lower (emphasis in the original) variance in the daily returns of the underlying stocks" Conversely, Kabir (1997) studying the Dutch market, Calado, Garcia and Pereira (2005) studying Portuguese markets and Mazouz and Bowe (2009) studying NYSE stocks listed on the CBOE find no significant change in risk following option listing.…”
Section: Hypothesis 2: Impact Of Options Listing On the Volatility Ofsupporting
confidence: 74%
“…Conversely, a decrease in volume is reported by Damodaran and Lim (1991) and no change in trading volume is documented by Whiteside, Dukes and Dunne (1983) and Chamberlin, Cheung, and Kwan (1993), the latter studying Canadian stocks. Heer, Trede, and Wahrenburg (1997) find an increase in volume in German markets, Chen and Chang (2008) report similar results in the Taiwan market as do Yip and Lai (2009), studying warrant listings in Malaysia. Kumar, Sarin and Shastri (1998) specifically find an increase in trading volume, trading frequency, and transaction size after option listing, an effect which persists even after controlling for changes in volatility and price.…”
Section: Hypothesis 3: Impact Of Options Listing On Trading Volume Ofsupporting
confidence: 68%
“…The empirical results found that positive abnormal returns existed, the degree of volatility decreased, trading volume increased and market depth also increased following the introduction of the stock options (Chena & Changb, 2008 Yu et al concluded that option introduction still has significant beneficial effects on stocks' trading and informational environment, even in a world where the great majority of large stocks have already been optioned (Yu, Tandon, & Webb, 2010).…”
Section: Previous Studiesmentioning
confidence: 99%
“…However, empirical evidence from his study on another developed market Japan, where individual stock options were introduced later than the index options, shows that listing of stock options still cause significant increases in volatility for the underlying stocks. Chen and Chang [16] Bollerslev [20], and Andersen & Bollerslev [21]. Their study shows that traditional tests of various volatility models which rely on ex-post squared (absolute) returns are a very noisy (although unbiased) estimate of volatilities.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, studies by Bhamra and Uppal[14] using option listing data from US, and Liu[5] using similar data on Japan, reports significant increase in the volatility of underlying stocks on the listing of option contracts. On the other hand, study by Chan and Chang[16] using option listing data from Taiwan reports decrease in volatility for the underlying asset market. Also, Dong, Fan, and Zhang [17] taking cross country and regions data from Asia, including mainland China, Japan, Hong Kong, Malaysia, Korea, Taiwan, and Singapore report short term increase in volatility.…”
mentioning
confidence: 97%